2011
DOI: 10.1007/s11262-011-0654-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibegomoviral activity of the agrobacterial virulence protein VirE2

Abstract: Mungbean yellow mosaic geminivirus (MYMV) causes severe yellow mosaic disease in blackgram, mungbean, Frenchbean, pigeonpea, soybean and mothbean. We attempted to induce resistance against this virus using the transcriptional activator protein gene deleted in the C-terminal activation domain (TrAP-∆AD) and Agrobacterium tumefaciens virE2. MYMV is known to replicate in agroinoculated tobacco leaf discs. Three transgenic tobacco plants which harboured a truncated MYMV transcriptional activator protein gene and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Thus, the Agrobacterium Ti plasmid virulence gene virE2 , encoding a nuclear ssDNA binding protein was expressed in N. benthamiana. The resulting transgenic plants were resistant to SLCMV (Resmi et al, 2015), in agreement with a report by Sunitha et al (2011) showing virE2 -mediated resistance to Mungbean yellow mosaic begomovirus (MYMV).…”
Section: Engineered Resistance To Cmgssupporting
confidence: 89%
“…Thus, the Agrobacterium Ti plasmid virulence gene virE2 , encoding a nuclear ssDNA binding protein was expressed in N. benthamiana. The resulting transgenic plants were resistant to SLCMV (Resmi et al, 2015), in agreement with a report by Sunitha et al (2011) showing virE2 -mediated resistance to Mungbean yellow mosaic begomovirus (MYMV).…”
Section: Engineered Resistance To Cmgssupporting
confidence: 89%
“…Thus, the Rep-binding peptide octamers may serve as an efficient strategy for engineering transgenic tomato plants that are resistant to diverse begomoviruses. Likewise, expression of the single-stranded DNA binding protein virE2 from Agrobacterium in tobacco has been shown to reduce Mungbean yellow mosaic virus DNA accumulation, although the spectrum of the resistance has not been established (Sunitha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sera [ 21 ] reported that expression of an artificial zinc finger protein targeting the replication origin of Beet severe curly top virus efficiently blocked viral DNA replication in transgenic Arabidopsis plants. Sunitha et al [ 22 ] expressed the A. tumefaciens Ti plasmid virE2 gene in tobacco and showed a reduction of viral DNA accumulation in leaf discs agroinoculated with Mungbean yellow mosaic virus (MYMV) partial dimers. Here, we report the efficacy of the virE2 gene in restricting SLCMV infection in transgenic Nicotiana benthamiana plants.…”
Section: Introductionmentioning
confidence: 99%